PERAN STAKEHOLDERS PROGRAM KOTA TANPA KUMUH (KOTAKU) DALAM PENANGANAN KAWASAN PERMUKIMAN KUMUH DI KELURAHAN DADAPSARI KOTA SEMARANG - Hawa Sahara; Ari Subowo; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Slums are a problem that is often found in urban areas. The government has made efforts to prevent and improve the quality of slums, one of which is through the Cities Without Slums (KOTAKU) Program. The KOTAKU program is implemented in 34 provinces and 271 districts/cities, including Semarang City. As of the end of 2022, the slum area in Dadapsari Village, Semarang City has not managed to reach the 0% target despite being made a priority for program handling. The slow implementation of construction and the remains of building materials that are left unattended are complaints from the local community. This research aims to analyze the role of KOTAKU Program stakeholders and the obstacles faced in handling slum areas in Dadapsari Village, Semarang City. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results show that Bappeda, Dinas Perumahan dan Kawasan Permukiman, and Tim Koordinator Kota KOTAKU play the role of key players. Meanwhile kecamatan, kelurahan, and BKM play the role of subjects. Obstacles faced include overlapping slum proposals and rejection of development proposals by the community to BKM in planning, ineffective coordination by the Tim Koordinator Kota KOTAKU due to job transfers, community resentment and unacceptance of the kelurahan, as well as difficulties in coordinating Bappeda with outside parties in implementation, kecamatan difficulties in overseeing undisciplined work and BKM in controlling the utilization of development results by the community.